1994
DOI: 10.1093/carcin/15.5.837
|View full text |Cite
|
Sign up to set email alerts
|

High promutagen activating capacity of yeast microsomes containing human cytochrome P-450 1A and human NADPH-cytochrome P-450 reductase

Abstract: Yeast Saccharomyces cerevisiae strains have been constructed that co-express cDNAs coding for the human cytochrome P-450 enzymes CYP1A1 or CYP1A2 in combination with human NADPH-cytochrome P-450 reductase (oxidoreductase). Microsomal fractions prepared from the strains were able to efficiently activate various drugs to Salmonella mutagens. These experiments demonstrated that a functional interaction occurred between the respective human enzymes in the yeast microsomes. For every drug tested, the microsomes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 42 publications
2
10
1
Order By: Relevance
“…This result is consistent with most of the earlier data, although previously applied assays may have had insufficient sensitivity to detect bioactivation by 1A1 or 1B1. The exceptional result of Sengstag et al [1994], who found that P450 forms 1A1 and 1A2 were similarly effective for activation of MeIQx, is inconsistent with our findings.…”
Section: Roles Of the P450 1 Family Enzymes In Bioactivation And Carccontrasting
confidence: 99%
“…This result is consistent with most of the earlier data, although previously applied assays may have had insufficient sensitivity to detect bioactivation by 1A1 or 1B1. The exceptional result of Sengstag et al [1994], who found that P450 forms 1A1 and 1A2 were similarly effective for activation of MeIQx, is inconsistent with our findings.…”
Section: Roles Of the P450 1 Family Enzymes In Bioactivation And Carccontrasting
confidence: 99%
“…Antigenic proteins have been detected in the transformed strains, and enzyme activity specific for the produced enzymes has been measured [27-301. In addition, microsomes prepared from the strains efficiently activated various promutagens to potentSalmonella mutagens [31]. Here we demonstrate that some of the drugs are also activated in intact yeast cells to products that significantly induce recombination.…”
mentioning
confidence: 67%
“…S9 fractions of yeast strains expressing hCYP1A2 or empty vector were prepared as previously described (86), except that growth conditions were modified to match those used in the cytotoxicity and mutagenicity studies. Specifically, 10 6 cells were grown for 7 h in 250 ml of synthetic media lacking uracil.…”
Section: Methodsmentioning
confidence: 99%